Estimating and comparing the implied cost of equity for Canadian and US firms - Jonathan Witmer; Lorie Zorn (Bank of Canada, 2007)
This paper estimates the implied cost of equity for Canadian and U.S. firms using a methodology based on the dividend discount model and utilizing firms' current stock price and analysts' forecasted earnings. We find that firm size and firm stock liquidity are negatively related to cost of equity, while greater firm financial leverage and greater dispersion in analysts' earnings forecasts are associated with a higher cost of equity. Moreover, longer-term sovereign bond yields also seem to play a role in a firm's cost of equity. After controlling for several factors, both at a firm-level and at an aggregate level, we find that the cost of equity for Canadian firms is 30-50 bps higher than that of U.S. firms during 1988-2006. Because our estimates may not fully account for factors such as currency risk, inflation uncertainty, degree of market integration, personal taxes, and differences in regulatory environments, we might shed further light on these results by incorporating proxies for these factors and perhaps extending our comparison to more countries.
Keywords: G30; G38; 330; Financial markets; International topics; Unternehmensfinanzierung; Eigenkapital; Kapitalkosten; Risikoprämie; Vergleich; USA; Kanada